2011
DOI: 10.1073/pnas.1106950108
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits determine trade-offs and niches in a tropical forest community

Abstract: How numerous tree species can coexist in diverse forest communities is a key question in community ecology. Whereas neutral theory assumes that species are adapted to common field conditions and coexist by chance, niche theory predicts that species are functionally different and coexist because they are specialized for different niches. We integrated biophysical principles into a mathematical plant model to determine whether and how functional plant traits and trade-offs may cause functional divergence and nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
211
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(230 citation statements)
references
References 47 publications
12
211
1
6
Order By: Relevance
“…2-4 and Fig. S1), not just at biome boundaries (43), and that there are continentalscale tradeoffs and correlations among traits (44). Our analysis is consistent with these viewpoints: for example, the emergent relationship between LCMA (proportional to leaf mass per area) and leaf lifespan (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…2-4 and Fig. S1), not just at biome boundaries (43), and that there are continentalscale tradeoffs and correlations among traits (44). Our analysis is consistent with these viewpoints: for example, the emergent relationship between LCMA (proportional to leaf mass per area) and leaf lifespan (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the contents of SC and starch were positively correlated with the contents of NH 4 N and FAA in M. spicatum, while negative relationships among these metabolites were observed in C. demersum in our study and reported for seagrass Gracilaria gracilis (Smit et al, 1996), indicating species-specific strategies in CN metabolism of the plants in response to external NH 4 + pulse. According to a trade-off of resource use, there are acquisitive and conservative strategies in plants; the former species are geared towards high resource acquisition rates and high growth rates, whereas, the latter species are geared towards high resource conservation, high stress tolerance, and high survival (Sterck et al, 2011). Previous studies revealed that M. spicatum showed higher growth rate and net assimilation rate (Fu et al, 2012), while C. demersum showed a more conservative C use strategy and higher NH 4 + stress and low light stress tolerance (Yuan et al, 2013;Zhong et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To prevent NH 4 + toxicity, many macrophytes decrease NH 4 + accumulation by incorporating it into free amino acids (FAA) and amines and/or by actively transporting it out of plant cells, which are processes requiring carbon (C) as energy and C-skeleton for FAA synthesis (Britto et al, 2001;Britto and Kronzucker 2002;Cao et al, 2009a), leading to imbalance of CN metabolism under NH 4 + stress, e.g., increases in NH 4 N and FAA and decreases in soluble carbohydrate (SC) and starch (Cao et al, 2009b;Zhang et al, 2010;Yuan et al, 2013). The effect of NH 4 + enrichment on plants depends on the C reserves, e.g., sufficient C reserves alleviated negative effects of NH 4 + enrichment on Zostera noltii and Potamogeton crispus (Brun et al, 2002;Cao et al, 2009b In this study, the submersed macrophytes Myriophyllum spicatum L. and Ceratophyllum demersum L. were used to test effects of NH 4 + pulse on their C and N metabolism, because (1) these species distributed worldwide and inhabit waters ranging from mesotrophic-to eutrophic-conditions (Aiken et al, 1979;Smith and Barko 1990;Mjelde and Faafeng 1997); (2) they prefer NH 4 + over NO 3 − (Nichols and Keeney 1976;Best 1980), and require a considerable quantity of N for biomass production (Goulder and Boatman 1971;Wersal and Madsen 2011); and (3) they represent two kinds of strategies in resource use (Poorter and Bongers 2006;Sterck et al, 2011), with M. spicatum having an acquisitive strategy and higher growth rate (Fu et al, 2012) and C. demersum having a conservative strategy, with a more conservative C use and higher tress tolerance (Yuan et al, 2013;Zhong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Where species occur along this axis is strongly governed by the partitioning of resource gradients, principally light Sterck et al 2006Sterck et al , 2011Wright et al 2010), as well as soil nutrients (Russo et al 2008). Consequently, species-specific adaptations to Abstract Adaptations to resource availability strongly shape patterns of community composition along successional gradients in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%